2017
DOI: 10.1097/md.0000000000007245
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of microRNA-107 targeting Dkk-1 by regulation of Wnt/β-catenin signaling pathway in osteosarcoma

Abstract: Background:The aim of the study was to explore the effects of microRNA-107 (miR-107) by targeting Dkk-1 on osteosarcoma (OS) via the Wnt/β-catenin signaling pathway.Methods:OS and adjacent tissues were collected from 67 patients diagnosed with OS. Expressions of miR-107, Dkk-1, LRP5, β-catenin, and c-Myc were detected by the quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting. The dual-luciferase reporter gene assay was performed to observe the relationship between miR-107 and Dkk-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Some studies have also shown Wnt signalling to be neuroprotective [114, 115]. Mir-107 has been shown to regulate Dkk1; however, this was in osteosarcoma [116].…”
Section: Network Analysis Of Deregulated Mirna At Braak Stage III In mentioning
confidence: 99%
“…Some studies have also shown Wnt signalling to be neuroprotective [114, 115]. Mir-107 has been shown to regulate Dkk1; however, this was in osteosarcoma [116].…”
Section: Network Analysis Of Deregulated Mirna At Braak Stage III In mentioning
confidence: 99%
“…In the present study, the protein expression levels of BAX, TP53 and caspase 3 were significantly increased, and those of TRIAP1 were decreased, in the miR-107 mimics group compared with the NC group. Therefore, it was hypothesized that miR-107 may induce the apoptosis of lung cancer cells by targeting TRIAP1 and increasing the expression levels of BAX, TP53 and caspase 3, which are three known tumor suppressors in lung cancer (32,33). Furthermore, previous studies have demonstrated that BCL2 knockdown decreased the viability and increased apoptosis of lung cancer cells (38), while overexpression of BCL2 decreased apoptosis of human lung cancer cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Du et al, [ 44 ] found that inhibition of miRNA- 184 may reduce tumor volume of osteosarcoma by regulating the Wnt /β- catenin signaling pathway. Zhang et al, [ 45 ] suggested that miR-107 inhibit development of osteosarcoma via the Wnt signaling pathway, and the critical role of miR- 214 in human osteosarcoma also through involving the Wnt signaling pathway. [ 46 ] Hence, it was proposed that miR-9-3p may possess a vital effect on osteosarcoma by Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%